Rhamnogalacturonan α-d-Galactopyranosyluronohydrolase : An Enzyme That Specifically Removes the Terminal Nonreducing Galacturonosyl Residue in Rhamnogalacturonan Regions of Pectin - Mutter, Margien (American Society of Plant Physiologists, 1998)
A new enzyme, rhamnogalacturonan (RG) α-d-galactopyranosyluronohydrolase (RG-galacturonohydrolase), able to release a galacturonic acid residue from the nonreducing end of RG chains but not from homogalacturonan, was purified from an Aspergillus aculeatus enzyme preparation. RG-galacturonohydrolase acted with inversion of anomeric configuration, initially releasing β-d-galactopyranosyluronic acid. The enzyme cleaved smaller RG substrates with the highest catalytic efficiency. A Michaelis constant of 85 μm and a maximum reaction rate of 160 units mg(−1) was found toward a linear RG fragment with a degree of polymerization of 6. RG-galacturonohydrolase had a molecular mass of 66 kD, an isoelectric point of 5.12, a pH optimum of 4.0, and a temperature optimum of 50°C. The enzyme was most stable between pH 3.0 and 6.0 (for 24 h at 40°C) and up to 60°C (for 3 h).